Preparation of ZnO nanoparticles: Structural study of the molecular precursor - Tokumoto, M. S.; Briois, V; Santilli, Celso Valentim [UNESP]; Pulcinelli, Sandra Helena [UNESP] (Kluwer Academic Publ, 2003)
The structure of zinc acetate derived precursor currently used in the sol-gel synthesis of ZnO nanoparticles is described. The reaction products obtained before and after reflux of ethanolic zinc acetate solution have been studied by UV-Vis, photoluminescence, FTIR and EXAFS at the Zn K edge. EXAFS results evidence for both precursor solutions a change from the octahedral coordination sphere of oxygen atoms characteristic of the solid zinc acetate dihydrate compound into a four-fold environment. The EXAFS spectra of precursor solutions can be satisfactorily reproduced using the molecular structure reported for Zn4O(Ac)(6) (Ac = COOCH3). UV-Vis and FTIR measurements are also in agreement with the formation of this oligomeric precursor. The structural modification is more pronounced after reflux at 80degreesC, because the increase of the Zn4O(Ac)(6) amount and the formation of nearly 3.0 nm sized ZnO nanoparticle.
Keywords: sol-gel precursor; ZnO nanoparticles; EXAFS